Introduction - Anheier, Helmut K.; Winder, David (Innovation in strategic philanthropy, 2007)
Most research on philanthropy and all but a few case studies on foundations are based on organizations and institutions in developed market economies, in particular the United States. While we have the beginnings of a knowledge base on philanthropy in Europe, Australia or Japan, we know very little about the role, operations, and above all, the innovative potential of philanthropy in other parts of the world. It is against this background that the chapters in this part have been written. What are the philanthropic cultures and practices in Central and Eastern Europe, Latin America, Africa and Asia, and how do they differ cross-nationally, and in particular from the US and Western European experience?